The Oxidation–Deuteration Processes of Large, Astronomically Relevant Cationic Polycyclic Aromatic Hydrocarbons - Xiaoyi Hu; Nian Zhao; Congcong Zhang; Xuejuan Yang; Alexander G. G. M. Tielens; Junfeng Zhen (The Astrophysical Journal)
In interstellar environments, gas-phase polycyclic aromatic hydrocarbon (PAH) predominantly involves (photo)fragmentation, hydrogenation, and oxidation chemical routes, which lead to the formation of complex organic species. Here the gas-phase reactions between tribenzo-naphtho-pero-pyrene (TNPP, C _40 H _18 ) cations and ultraviolet, ^18/16 O or D atoms are investigated. The oxidized TNPP cations ([C _40 H _18/17/16 O _n ] ^+ , n = [1, 6]) are newly formed; the collision-induced deoxidation of oxidized TNPP cations is followed by the loss of HCO/CO units. With laser irradiation, the photo-deoxidation of oxidized TNPP cations is identified. Smaller PAH cations, [C _40− _n H _18− _n ] ^+ , with n = [1, 5], i.e., PAHs containing odd carbon numbers (e.g., 39, 37 C atoms), are produced. Furthermore, the oxidized–deuterated TNPP cations ([C _40 H _m D _n O _x ] ^+ ) are well formed upon simultaneous reaction with O and D atoms. The structure of the oxidized–deuterated TNPP cations and the bonding energy for these reaction pathways were investigated with theoretical calculations. Four oxidation bonding types are identified together with their evolution pathways. The reaction energy is relatively high, and the addition of O/D atoms to the carbon skeleton is a relatively random and independent event, i.e., with no restrictions or requirements for the carbon sites of PAH species. Consequently, the oxidized–deuterated states and forms of PAH compounds are intricate and complex. Furthermore, the calculations confirm that the loss of CO or H+CO is energetically preferable. Importantly, the formation of the carbonyl unit is confirmed. We infer that the collision/photo-induced deoxidation (loss of (H)CO units) of oxidized PAH species is involved in the top-down evolution routes of large PAHs and effectively catalyzes the potential formation of small oxygen-containing species (e.g., OH/HCO/CO) in the interstellar medium.